Predictors of the discrepancy between objective and subjective cognition in bipolar disorder: a novel methodology. (20th September 2016) - Miskowiak, K. W.; Petersen, J. Z.; Ott, C. V.; Knorr, U.; Kessing, L. V.; Gallagher, P.; Robinson, L.
Abstract : Objective: The poor relationship between subjective and objective cognitive impairment in bipolar disorder (BD) is well‐established. However, beyond simple correlation, this has not been explored further using a methodology that quantifies the degree and direction of the discrepancy. This study aimed to develop such a methodology to explore clinical characteristics predictive of subjective‐objective discrepancy in a large BD patient cohort. Methods: Data from 109 remitted BD patients and 110 healthy controls were pooled from previous studies, including neuropsychological test scores, self‐reported cognitive difficulties, and ratings of mood, stress, socio‐occupational capacity, and quality of life. Cognitive symptom 'sensitivity' scores were calculated using a novel methodology, with positive scores reflecting disproportionately more subjective complaints than objective impairment and negative values reflecting disproportionately more objective than subjective impairment ('stoicism'). Results: More subsyndromal depressive and manic symptoms, hospitalizations, BD type II, and being male positively predicted 'sensitivity', while higher verbal IQ predicted more 'stoicism'. 'Sensitive' patients were characterized by greater socio‐occupational difficulties, more perceived stress, and lower quality of life. Conclusion: Objective neuropsychological assessment seems especially warranted in patients with (residual) mood symptoms, BD type II, chronic illness, and/or high IQ for correct identification of cognitive deficits before commencement of treatments targeting cognition.